Tożsamość organizacyjna a funkcjonowanie menedżera w środowisku pracy - Kozak, Agnieszka; Ostrowska, Iwona (Organizational identity and the manager's functioning in the work environment, 2006)
The problem of selection and evaluation of the international organizations’ staff is connected with the ability to estimate the universal features of an international organization and its requirements towards the managerial staff. There does not exist one international organization, as each of such companies may be characterized by its own specific organizational identity. To recognize the organizational identity of the company is an important task, as it allows the managers to identify with the organization. Organizational identity may be reproduced by surveying the attitudes and values of its employees. The paper presents the results of perceiving the organizational identity in two branches of the same organization. The data show that even in one firm, but in its different branches, the organizational identity may be different. Effective management of the managerial staff in an international organization may be based on recognizing the identity of this organization and projecting such changes in the organizational culture that will aim at the identification of an individual with an organization. It is of an utmost importance as correlation is found between identification with an organization and job satisfaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 53-60